Performance Evaluation of a 250 Wp Solar Photovoltaic Water Pumping System in Tropical Climate: A Case Study in Pangkalan Kerinci, Indonesia - Rien Afrianti; Dedi Tri Laksono; Deni Tri Laksono; Monika Faswia Fahmi (International Journal of Science, Engineering, and Information Technology, 2025)
Access to clean water in remote tropical regions remains a critical challenge, particularly where grid electricity is unavailable. Solar photovoltaic (PV) water pumping systems offer a sustainable, off-grid solution. This study evaluates the technical performance of a 250 Wp PV-powered deep well water pumping system installed in Pangkalan Kerinci, Indonesia (0.41°N, 101.85°E). The system employs a single Trina Solar TSM-310PD14 module connected to a Sun Pumps SDS-D-128 DC membrane pump via an MPPT controller. Using PVSyst v7.4.6, a one-year simulation was conducted under realistic meteorological and hydraulic conditions, including a static water table at 4 m depth and a daily water demand of 0.30 m³. Results indicate that the system reliably meets annual water needs (109 m³/year) with negligible water deficit (0.163 m³, or 0.15%). The annual specific water yield is 522 m³/kWp/bar, while the system operates at an overall efficiency of 4.3% and a pump efficiency of 16.7%. Energy analysis shows 15.5 kWh/year delivered to the pump, with 42.6 kWh/year of excess solar energy unused due to tank capacity limits. The performance ratio (PR) is approximately 87%, confirming high system reliability in equatorial conditions. This study demonstrates the technical viability of small-scale solar pumping for rural water supply in Indonesia.